2008
DOI: 10.1111/j.1471-0528.2008.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of acupuncture in in vitro fertilisation

Abstract: Background Numerous randomised studies have reported pregnancy outcome in women who received acupuncture during their in vitro fertilisation (IVF) treatment cycle.Objective The objective of this study was to conduct a systematic review with meta-analysis of the trials of acupuncture during IVF treatment on the outcomes of clinical pregnancy and live birth rates.Search strategy Searches were conducted in MEDLINE, EMBASE, Cochrane Library, ISI Proceedings and SCISEARCH.Selection criteria All randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 44 publications
1
83
2
6
Order By: Relevance
“…Early research suggests that prayer [17], yoga [18], acupuncture [19], stress avoidance [20], and having a positive attitude [5], might positively impact success, though studies have not elucidated whether an effect is achieved through direct or indirect mechanism. Data exists to suggest acupuncture might improve outcomes through the mechanism of stress reduction [19], though a more substantial body of research does not support an independent relationship whereby acupuncture improves IVF outcomes [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Early research suggests that prayer [17], yoga [18], acupuncture [19], stress avoidance [20], and having a positive attitude [5], might positively impact success, though studies have not elucidated whether an effect is achieved through direct or indirect mechanism. Data exists to suggest acupuncture might improve outcomes through the mechanism of stress reduction [19], though a more substantial body of research does not support an independent relationship whereby acupuncture improves IVF outcomes [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In another systematic review it was suggested that the currently available literature does not provide suffi cient evidence that adjuvant acupuncture improves assisted reproduction clinical pregnancy rate. 24 Wang et al 29 performed 30 min acupuncture sessions starting on day 5 of the cycle until 2 weeks after oocyte retrieval and found no improvement in the pregnancy rate. Most of the studies reporting positive effects of acupuncture on ICSI outcomes performed the sessions immediately before embryo transfer, unlike in Wang's study.…”
Section: Discussionmentioning
confidence: 99%
“…22 23 A recent systematic review and meta-analysis of acupuncture in IVF has demonstrated that the currently available literature does not provide sufficient evidence that adjuvant acupuncture improves assisted reproduction clinical pregnancy rate. 24 Conversely, other meta-analyses have suggested that acupuncture given with embryo transfer improves rates of pregnancy and live birth among women undergoing IVF. 25 In another systematic review, Cheong et al 26 suggested that acupuncture performed on the day of embryo transfer has a benefi cial effect on the live birth rate; however, with the present evidence this could be attributed to placebo effect.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 Individualised pattern diagnoses (based on signs and symptoms) and treatment according to their individual patterns are important features of acupuncture rooted in traditional Chinese medicine (TCM). [5][6][7][8] To ensure consistent and optimal treatment the pattern diagnoses must be reliable, but only a few studies have assessed the reliability of diagnostic data collected during a TCM examination. 9 O'Brien and Birch reviewed studies of the reliability of traditional East Asian medicine diagnoses and concluded that reliability of pattern diagnoses and treatment was low.…”
Section: Introductionmentioning
confidence: 99%